The burning god - Kuang, R. F. (Rebecca F.) (Kuang, R. F. (Rebecca F.) Poppy war, 2020)
Rin returns to her home village, where with the Southern Army and millions of dedicated supporters she prepares for the ultimate battle against the Dragon Republic and other anti-shamanic enemies.